The Pancasila and Civic Education curriculum model at 21st century - Jayadiputra, Eka; Karim, Aim Abdul; Sapriya, Sapriya; Rahmat, Rahmat (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
The challenge of producing highly competitive and superior human resources is faced by nations worldwide, including Indonesia's education sector, specifically in Civic Education. Enhancing the quality of education requires a reconstructed curriculum that includes 21st-century competencies. This study aimed to describe the design model for developing citizenship skills in the current century. The research adopted a qualitative descriptive and quasi-experimental approach, collecting data through questionnaires, interviews, observations, documentation studies, and literature reviews. The sample comprised 180 high school students and Civic Education teachers from three schools in Bandung Regency. Findings showed that students' skills in Civic Education using the 2013 curriculum were suboptimal. However, the experimental group using the 21st-century curriculum exhibited a significant increase in their skills, including learning and innovation skills, life and career skills, and technology and media skills. Improving Civic Education in Indonesia is crucial in nurturing competent and competitive citizens.